Improved Routing Protocol Based on Multiobjective Optimization in Industrial Robot Networks - You Wu Liu; Syazwina Binti Alias; Ming-yue Liu; Bian-bian Jiao (Advances in Multimedia)
This paper decomposes the routing process of industrial robot network using the application of analytic hierarchy process in decision-making. The influence of four factors, such as path length, data integrity, energy consumption, and receiving delay, on routing effect is analyzed. Simultaneous interpreting routes are selected to achieve the purpose of routing. Simulation results show that this method can more comprehensively consider the factors affecting routing and is superior to the existing methods in terms of energy consumption, data integrity, and transmission delay.